Diagnosing autoimmune pancreatitis with the Unifying-Autoimmune-Pancreatitis-Criteria - Schneider, Alexander; Michaely, Henrik J. M.; Rückert, Felix; Weiß, Christel; Ströbel, Philipp; Belle, Sebastian; Hirth, Michael; Wilhelm, Torsten; Jesenofsky, Ralf; Schönberg, Stefan; Marx, Alexander; Singer, Manfred V.; et al. (Pancreatology, 2017)
Background/Objectives: We had developed the Unifying-Autoimmune-Pancreatitis-Criteria (U-AIP) to diagnose autoimmune pancreatitis (AiP) within the M-ANNHEIM classification of chronic pancreatitis. In 2011, International-Consensus-Diagnostic-Criteria (ICDC) to diagnose AiP have been published. We had applied the U-AIP long before the ICDC were available. The aims of the study were, first, to describe patients with AiP diagnosed by the U-AIP; second, to compare diagnostic accuracies of the U-AIP and other diagnostic systems; third, to evaluate the clinical applicability of the U-AIP. Methods: From 1998 until 2008, we identified patients with AiP using U-AIP, Japanese-, Korean-, Asian-, Mayo-HISORt-, Revised-Mayo-HISORt- and Italian-criteria. We retrospectively verified the diagnosis by ICDC and Revised-Japanese-2011-criteria, compared diagnostic accuracies of all systems and evaluated all criteria in consecutive patients with pancreatitis (2009 until 2010, Pancreas-Outpatient-Clinic-Cohort, n = 84). We retrospectively validated our diagnostic approach in consecutive patients with a pancreatic lesion requiring surgery (Surgical-Cohort, n = 98). Results: Overall, we identified 21 patients with AiP. Unifying-Autoimmune-Pancreatitis-Criteria and ICDC presented the highest diagnostic accuracies (each 98.8%), highest Youden indices (each 0.95238), and highest proportions of diagnosed patients (each n = 20/21, U-AIP/ICDC vs. other diagnostic systems, p < 0.05, McNemar test). In the Pancreas-Outpatient-Clinic-Cohort, seven patients were diagnosed with AiP (n = 6 by U-AIP, n = 1 by Asian-criteria). International-Consensus-Diagnostic-Criteria confirmed the diagnosis in these individuals. Based on partial fulfillment of U-AIP, AiP was initially suspected in 13% (n = 10/77) of remaining patients from the Pancreas-Outpatient-Clinic-Cohort. In the Surgical-cohort, we identified one patient with AiP by U-AIP and ICDC. Conclusions: Unifying-Autoimmune-Pancreatitis-Criteria revealed a satisfactory clinical applicability and offered an additional approach to diagnose AiP.